INHIBITIVE EFFECT OF DATE EXTRACT ON THE CORROSION OF CARBON STEEL IN ACIDIC MEDIA - Moussaoui, Naima; Zerouali, Djilali; Bettahar, Noureddine (Journal of the Chilean Chemical Society, 2017)
The inhibitive effect of date extract on the corrosion of Carbon steel in 1M HCl solution has been investigated by weight loss measurement, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. The presence of this extract reduces remarkably the corrosion rate of mild steel in acidic solution. The inhibition efficiency was found to increase with increasing inhibitor concentrations due to the adsorption of the inhibitor molecules on the metal surface, this adsorption follows Langmuir’s adsorption isotherm. The inhibition efficiency was found to be 85.84% at 1.5V/V% in 1M HCl. Temperature studies revealed a decrease in efficiency with rise in temperature.